2004
DOI: 10.1093/hmg/ddh193
|View full text |Cite
|
Sign up to set email alerts
|

Association and regulation of the BLM helicase by the telomere proteins TRF1 and TRF2

Abstract: In addition to increased DNA-strand exchange, a cytogenetic feature of cells lacking the RecQ-like BLM helicase is a tendency for telomeres to associate. We also report additional cellular and biochemical evidence for the role of BLM in telomere maintenance. BLM co-localizes and complexes with the telomere repeat protein TRF2 in cells that employ the recombination-mediated mechanism of telomere lengthening known as ALT (alternative lengthening of telomeres). BLM co-localizes with TRF2 in foci actively synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 47 publications
3
144
1
2
Order By: Relevance
“…It is noteworthy that PML bodies that contain DNA in ALT cells, also called APBs, not only contain Smc5/6 (Potts and Yu 2007) but also require Smc5/6-dependent SUMOylation of the shelterin complex, an event thought to mediate the recruitment of telomere repeats to APBs (Potts and Yu 2007). Moreover, BLM has been implicated in ALT pathways, localizes to APBs, and interacts with the shelterin subunits TRF1 and TRF2 (Stavropoulos et al 2002;Lillard-Wetherell et al 2004;Zimmermann et al 2014), and its overexpression promotes increased telomeric HR and longer telomeres (Stavropoulos et al 2002). It is tempting to speculate that Smc5/6 might promote telomeric recombination in ALT cells by coordinating recruitment of telomeres and BLM to APBs and activating the prorecombinogetic role of BLM in a manner analogous to what we demonstrated here for Sgs1.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that PML bodies that contain DNA in ALT cells, also called APBs, not only contain Smc5/6 (Potts and Yu 2007) but also require Smc5/6-dependent SUMOylation of the shelterin complex, an event thought to mediate the recruitment of telomere repeats to APBs (Potts and Yu 2007). Moreover, BLM has been implicated in ALT pathways, localizes to APBs, and interacts with the shelterin subunits TRF1 and TRF2 (Stavropoulos et al 2002;Lillard-Wetherell et al 2004;Zimmermann et al 2014), and its overexpression promotes increased telomeric HR and longer telomeres (Stavropoulos et al 2002). It is tempting to speculate that Smc5/6 might promote telomeric recombination in ALT cells by coordinating recruitment of telomeres and BLM to APBs and activating the prorecombinogetic role of BLM in a manner analogous to what we demonstrated here for Sgs1.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that the C-terminal fragment of BLM, encompassing the RQC and HRDC domains, is necessary for the interaction with the telomere-associated protein, TRF2, which stimulates BLM-mediated unwinding of two telomere substrates in vitro; a 3Ј-overhang and a telomere D-loop structure (Lillard-Wetherell et al, 2004). Collectively, these studies indicate that the HRDC domain plays an important role both in conferring some specific enzymatic activities to the individual RecQ enzymes and in DNA structure-specific recognition.…”
Section: The Helicase-and-rnased-like-c-terminal Domainmentioning
confidence: 99%
“…It has been shown that TRF1 counts and controls the length of telomere repeats, probably through its interaction with TIN2, Tankyrase, PINX1, TPP1, and POT1 (7,9,12,15,(17)(18)(19)(20)(21)(22)(23)(24). In comparison, TRF2 has an essential role in end protection and the telomeric recruitment of several proteins, including the BRCA1 Cterminal domain-containing protein RAP1, the nucleotide excision repair protein ERCC1͞XPF, BLM, and the DNA repair MRN complex (24)(25)(26)(27)(28)(29)(30)(31). Because of their abilities to interact with multiple proteins, TRF1 and TRF2 are by definition hubs of protein-protein interaction at the telomeres (32).…”
mentioning
confidence: 99%